The economic globalization of sports - Bendkfal, rachid (sports creativity, 2025)
The relationship between economics and sports dates back to the ancient Olympic Games of Greece in 776 BC. These games continued for over a thousand years, held every four years, until they were discontinued by order of the Roman Emperor Theodosius. Organized sports practice continued intermittently until the 19th century, when sports were reorganized on clear principles, giving birth to modern football. The modern Olympic Games were then revived, largely thanks to the efforts of the Frenchman Pierre de Coubertin. This led to the development of gambling on the results of sporting activities and the rise of professional sports, ultimately giving rise to the economics of sports.